Size of Patent Ductus Arteriosus and Echocardiographic Markers of Shunt Volume in Preterm Infants Based on Postnatal Age - Choi, Eui Kyung; Park, Kyu Hee; Choi, Byung Min (Frontiers in Pediatrics, 2021)
Objective: To compare the strength of correlation between echocardiographic markers of shunt volume and patent ductus arteriosus (PDA) diameter based on postnatal age. Methods: This retrospective study focused on preterm infants (aged <32 weeks of gestation) admitted to the Neonatal Intensive Care Unit of Korea University Ansan Hospital, between April 2014 and December 2017, who studied serial targeted neonatal echocardiography (TNE) for PDA during hospitalization. The association between echocardiographic characteristics and duct size was divided into the following days: within 3 days (Very Early, VE), 4-7 days after birth (Early, E), and after 8 days of birth (Late, L). Results: We found 113 assessments conducted on 57 infants in the VE period, 92 assessments on 40 infants in the E period, and 342 assessments on 37 infants in the L period. Median gestational age and birth weight were 28+2 weeks of gestation and 1,115 g, respectively. In the univariate regression analysis, we found a statistically significant correlation between PDA diameter and all TNE markers in the E and L days, but not in the VE period. Only ductal velocity (coefficient of determination [R²] = 0.224), antegrade left pulmonary artery diastolic flow velocity (R² = 0.165), left ventricular output (LVO)/superior vena cava (SVC) flow ratio (R² = 0.048), and E/A wave ratio (R² = 0.092) showed weak correlations with PDA diameter in the VE period. The slopes of the regressions showed significant changes based on postnatal age in the maximum ductal velocity, left atrium/aorta ratio, LVO/SVC flow ratio, and the LVO. Conclusions: It is difficult to predict the echocardiographic markers of shunt volume based on the PDA diameter in preterm infants younger than 4 days. A better understanding of changes in the hemodynamic consequences of PDA based on postnatal age is needed when considering treatment.